Amid play games and commemoration: infant social experience in Isola Sacra (1st and 2nd centuries CE) - Omena, Luciane Munhoz de (Romanitas - Revista de Estudos Grecolatinos, 2020)
The paper aims at reflecting on infant socialization in the Roman Mediterranean, especially in the necropolis of Isola Sacra, located between Ostia and Portus. The presence of children is verified in the funereal site. Boys and girls are seen as commemorated in a wide range of mediums such as steles, altars, portraits, sarcophagi, which portray the mourning, the feeling of loss, individuality and their entertainment, birth, education environments, among others. From these observations, therefore, it is proposed to understand infant social experience in written testimonies and material related to jesting and educating. In a second stage, the study engages towards funeral commemoration for the children in existing epitaphs in Isola Sacra.
Keywords: Social Experience; Play Games; Death; Infants; Epitaphs